2011 IEEE International 3D Systems Integration Conference (3DIC), 2011 IEEE International 2012
DOI: 10.1109/3dic.2012.6263016
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and bonding process of fine pitch Cu pillar bump on thin Si chip for 3D stacking IC

Abstract: Abstracts3D packaging technology has been studied actively due to requirement of high performance, high density, and multifunction on electronic devices. This study investigated formation and bonding process of ultra-fine Cu pillar bump on both sides of Si thin wafer for 3D IC. Thickness of the thin wafer was 100μm. The bumps for the interconnection were formed as Sn-3.5Ag cap bump on Cu pillar bump by electroplating method. The diameter and height of the bump were 20μm, respectively. Thin Si chip was joined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In particular, since a fine pitch size causes solder bridging, an existing junction structure has limitation in decreasing its package size. Recently Ki et al [10] has reported an ultra fine pitch Cu pillar bump with a solder cap bump on Cu pillar bump. This study indicates that a junction structure with an ultra fine pitch Cu pillar bump below 40 lm diameter for TSV (through Silicon via) and Chip-on-Chip (CoC) can solve the problems of a solder bridging phenomena and a low mechanical strength caused by low standoff height.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, since a fine pitch size causes solder bridging, an existing junction structure has limitation in decreasing its package size. Recently Ki et al [10] has reported an ultra fine pitch Cu pillar bump with a solder cap bump on Cu pillar bump. This study indicates that a junction structure with an ultra fine pitch Cu pillar bump below 40 lm diameter for TSV (through Silicon via) and Chip-on-Chip (CoC) can solve the problems of a solder bridging phenomena and a low mechanical strength caused by low standoff height.…”
Section: Introductionmentioning
confidence: 99%
“…Recent improvements in performance and node size decrease in semiconductors lead to a lowering in the bump pitch of the semiconductor package [ 1 , 2 , 3 ]. The fine-pitch semiconductor packages have brought about a huge change in the flip-chip bonding process and materials.…”
Section: Introductionmentioning
confidence: 99%
“…ICs are often the primary source of radiated emissions, and near field magnetic field can help engineers to track down EMI culprit and solve the . Three-dimensional stack-dies integrated circuits (3D-ICs) trend for vertical distance between ICs [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%